(untitled) (South East Asia Journal of Public Health, 2015)
Hepatitis B is the most important infectious occupational hazard which the healthcare workers (HCWs) encounter. Healthcare personnel specially nursing staff represents a high risk population for HBV infection. The objective of the study was to assess the level of preventive practices regarding Hepatitis B among nurses and the factors associated with preventive practices. The study was conducted among 300 nurses both from public and private hospitals using a pretested structured questionnaire adopting a purposive sampling technique. The mean age of the respondents was 29.7±5.8 and majority of them (83.7%) were holding Diploma degrees with (83.3%) designated as staff nurse. About 59.7% were married and 94.3% were females. One third of the respondents (34.3%) were from public institution and 65.7% from private institution. It was revealed from the study that (67.3%) of the respondents had adequate level of knowledge on Hepatitis B but only half of them (49.3%) had good level of preventive practices. Bivariate analysis showed association between institution, income, age, religion, knowledge and level of preventive practice (P<0.05). In conclusion it can be said that compared to knowledge of the respondents on Hepatitis B, their preventive practices were low. Appropriate educational and health promotion programs should be implemented to increase the level of preventive practices on Hepatitis B among the nurses. DOI: http://dx.doi.org/10.3329/seajph.v4i1.21840 South East Asia Journal of Public Health Vol.4(1) 2014: 48-52